IMPLIKASI RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SUB-SEKTOR ROKOK - Erly Sherlita; Dadin Solihin; Marwan Fauzi (FEBI UIN Sunan Gunung Djati Bandung, 2022)
This study was conducted to test the effect of Return on Asset (ROA), Return on Equity (ROE), and Earning per Share (EPS) on stock prices in cigarette sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2021 period. This research was motivated by several increases in ROA, ROE, and EPS, but was not followed by rising stock prices, as well as research gaps. This research method is in the form of a quantitative method. The research population is cigarette sub-sector manufacturing companies listed on the IDX for the 2015-2021 period totaling 31 company financial statements. This study used the Ordinary Least Square (OLS) analysis method. As a result, ROA, ROE, and EPS simultaneously have a positive and significant effect on the stock price, while partially ROA, and ROE, also do not affect the stock price. In contrast to EPS, it has a positive and significant effect on stock prices. This condition became a novelty for the author to put forward, even though advertisements for the dangers of cigarettes were published in almost every media.